2003
DOI: 10.1177/1077559502239612
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Victimization Severity and Outcomes Among Adolescents Treated for Substance Abuse

Abstract: This article uses data from the Global Appraisal of Individual Needs (GAIN) on 214 adolescents entering substance abuse treatment. The goals of the article are to validate the General Victimization Index (GVI), examine its relationship to gender and co-occurring problems, and determine its relationship to outcomes. The GVI includes 15 items on lifetime traumatic events, traumagenic factors, and current worries of victimization. The items fall along a severity dimension (alpha = .88), and evidence was generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
69
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 82 publications
15
69
0
Order By: Relevance
“…These results agree with the results that have emerged in previous studies (13,20,28,(30)(31)(32). The prevalence of various types of exposure to violence is also generally high among the target group and varies from 11% to 45%.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results agree with the results that have emerged in previous studies (13,20,28,(30)(31)(32). The prevalence of various types of exposure to violence is also generally high among the target group and varies from 11% to 45%.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have shown that the exposure of children and adolescents to violence or experiences of victimization has a significant correlation with drug abuse later in life (6,20). This group commonly initiates substance use earlier, uses multiple substances more frequently and at a higher rate (18,19), and develops substance-abuse-related problems more often (19).…”
Section: Victimization In Relation To Drug and Alcohol Usementioning
confidence: 99%
See 3 more Smart Citations